Cannabinoid signalling inhibits sarcoplasmic Ca(2+) release and regulates excitation-contraction coupling in mammalian skeletal muscle. - Olah, Tamas; Bodnar, Dora; Toth, Adrienn; Vincze, Janos; Fodor, Janos; Reischl, Barbara; Kovacs, Adrienn; Ruzsnavszky, Olga; Dienes, Beatrix; Szentesi, Peter; Friedrich, Oliver; Csernoch, Laszlo (The Journal of Physiology, 2016)
KEY POINTS Marijuana was found to cause muscle weakness, although the exact regulatory role of its receptors (CB1 cannabinoid receptor; CB1R) in the excitation-contraction coupling (ECC) of mammalian skeletal muscle remains unknown. We found that CB1R activation or its knockout did not affect muscle force directly, whereas its activation decreased the Ca(2+) -sensitivity of the contractile apparatus and made the muscle fibres more prone to fatigue. We demonstrate that CB1Rs are not connected to the inositol 1,4,5-trisphosphate pathway either in myotubes or in adult muscle fibres. By contrast, CB1Rs constitutively inhibit sarcoplasmic Ca(2+) release and sarcoplasmic reticulum Ca(2+) ATPase during ECC in a Gi/o protein-mediated way in adult skeletal muscle fibres but not in myotubes. These results help with our understanding of the physiological effects and pathological consequences of CB1R activation in skeletal muscle and may be useful in the development of new cannabinoid drugs. ABSTRACT Marijuana was found to cause muscle weakness, although it is unknown whether it affects the muscles directly or modulates only the motor control of the central nervous system. Although the presence of CB1 cannabinoid receptors (CB1R), which are responsible for the psychoactive effects of the drug in the brain, have recently been demonstrated in skeletal muscle, it is unclear how CB1R-mediated signalling affects the contraction and Ca²⁺ homeostasis of mammalian skeletal muscle. In the present study, we demonstrate that in vitro CB1R activation increased muscle fatigability and decreased the Ca(2+) -sensitivity of the contractile apparatus, whereas it did not alter the amplitude of single twitch contractions. In myotubes, CB1R agonists neither evoked, nor influenced inositol 1,4,5-trisphosphate (IP3 )-mediated Ca(2+) transients, nor did they alter excitation-contraction coupling. By contrast, in isolated muscle fibres of wild-type mice, although CB1R agonists did not evoke IP3 -mediated Ca(2+) transients too, they significantly reduced the amplitude of the depolarization-evoked transients in a pertussis-toxin sensitive manner, indicating a Gi/o protein-dependent mechanism. Concurrently, on skeletal muscle fibres isolated from CB1R-knockout animals, depolarization-evoked Ca(2+) transients, as well qas Ca(2+) release flux via ryanodine receptors (RyRs), and the total amount of released Ca(2+) was significantly greater than that from wild-type mice. Our results show that CB1R-mediated signalling exerts both a constitutive and an agonist-mediated inhibition on the Ca(2+) transients via RyR, regulates the activity of the sarcoplasmic reticulum Ca(2+) ATPase and enhances muscle fatigability, which might decrease exercise performance, thus playing a role in myopathies, and therefore should be considered during the development of new cannabinoid drugs.